Flame retardant polypropylene based composites - Lee, Jocelyn Jia Min (Nanyang Technological University, 2021)
In this final year project, the work is focused on polypropylene (PP) based carbon fiber reinforced composite system with minimal loading of intumescent flame retardant additives (IFR) into PP matrix. Several modifications were studied on the traditional ammonium polyphosphate (APP) based IFR by adding melamine polyphosphate (MPP), titanium dioxide (TiO2), and carbon black (CB) to achieve better flame retardancy performance with and without the presence of long fiber mats. Several characterisation tools and test were used to analyse the thermal properties of the samples. Thermalgravimatric analyser (TGA) are used to study the decomposition temperature and residues of the samples. Pyrolysis combustion flow calorimeter (PCFC) was used to study the peak heat release rate and total heat release rate of the samples after combustion. UL94, the Standard for Safety of Flammability of Plastic Materials for Parts in Devices and Appliances testing, was conducted to study the flammability rating of the polymer samples.